Reading and re-reading Scripture at Qumran - Bernstein, Moshe J. (Studies on the Texts of the Desert of Judah, 2013)
In Reading and Re-reading Scripture at Qumran , Moshe J. Bernstein gathers more than three decades of his work on diverse aspects of biblical interpretation in the Dead Sea Scrolls. The essays range from broad surveys of the genres of biblical interpretation in these texts to more narrowly focused studies and close readings of specific documents. Volume I focuses on the book of Genesis, with a substantial portion being dedicated to studies of the Genesis Apocryphon and Commentary on Genesis A. Volume II contains several historical and programmatic essays, with specific studies focusing on legal material in the DSS and the pesharim. Under the former rubric, the documents known as 4QReworked Pentateuch, 4QOrdinancesa, 4QMMT, and the Temple Scroll are discussed.